Analysis of heart sound signals in ebstein's anomaly - AKGÜN, ÖMER (My University, 2022)
Ebstein's anomaly is an abnormality in the pediatric heart disease group. The anomaly is described as a structural defect by considering the whole heart. It can be manifested by typical symptoms in auscultation and can be detected with other diagnostic methods such as ECG. Systolic ejection click and murmur are the most important symptoms in the diagnosis of disease. In this study, heart sound signal recorded from a 13-year-old patient was analyzed with different numerical methods along with a normal heart sound signal. The signals were first examined in the time plane and findings in auscultation were observed. The frequency components of the signals were then obtained. Additional frequency components emerged in findings of disease in this plane compared to the normal one. Spectrograms enable to observe the differences in time frequency and amplitude components. Bispectral analysis was performed as a high order spectral analysis method by diversifying the analysis. In bispectral analysis of the anomaly, click and murmurs are manifested by equiphase surfaces distributed at high frequencies.Lastly, the power spectrum density of the signals were examined. The
Keywords: Ebstein's anomaly; Heart sound signals; Time frequency analyses; Bispectrum; Power spectrum density